Size‐dependent hygroscopicity parameter (κ) and chemical composition of secondary organic cloud condensation nuclei. Issue 24 (19th December 2015) - Zhao, D. F.; Buchholz, A.; Kortner, B.; Schlag, P.; Rubach, F.; Kiendler‐Scharr, A.; Tillmann, R.; Wahner, A.; Flores, J. M.; Rudich, Y.; Watne, Å. K.; Hallquist, M.; et al.
Abstract: Secondary organic aerosol components (SOA) contribute significantly to the activation of cloud condensation nuclei (CCN) in the atmosphere. The CCN activity of internally mixed submicron SOA particles is often parameterized assuming a size‐independent single‐hygroscopicity parameter κ . In the experiments done in a large atmospheric reactor (SAPHIR, Simulation of Atmospheric PHotochemistry In a large Reaction chamber, Jülich), we consistently observed size‐dependent κ and particle composition for SOA from different precursors in the size range of 50 nm–200 nm. Smaller particles had higher κ and a higher degree of oxidation, although all particles were formed from the same reaction mixture. Since decreasing volatility and increasing hygroscopicity often covary with the degree of oxidation, the size dependence of composition and hence of CCN activity can be understood by enrichment of higher oxygenated, low‐volatility hygroscopic compounds in smaller particles. Neglecting the size dependence of κ can lead to significant bias in the prediction of the activated fraction of particles during cloud formation. Key Points: CCN activity (hygroscopicity parameter kappa) of SOA decreased with particle size The degree of oxidation of SOA decreased with particle size Neglecting size‐dependent kappa can significantly affect predicted CCN concentration